Multiple horizontal transfers of nuclear ribosomal genes between phylogenetically distinct grass lineages - Mahelka, Václav; Krak, Karol; Kopecký, David; Fehrer, Judith; Šafář, Jan; Bartoš, Jan; Hobza, Roman; Blavet, Nicolas; Blattner, Frank R (Proceedings of the National Academy of Sciences of the United States of America, 2017)
The movement of nuclear DNA from one vascular plant species to another in the absence of fertilization is thought to be rare. Here, nonnative rRNA gene [ribosomal DNA (rDNA)] copies were identified in a set of 16 diploid barley (Hordeum) species; their origin was traceable via their internal transcribed spacer (ITS) sequence to five distinct Panicoideae genera, a lineage that split from the Pooideae about 60 Mya. Phylogenetic, cytogenetic, and genomic analyses implied that the nonnative sequences were acquired between 1 and 5 Mya after a series of multiple events, with the result that some current Hordeum sp. individuals harbor up to five different panicoid rDNA units in addition to the native Hordeum rDNA copies. There was no evidence that any of the nonnative rDNA units were transcribed; some showed indications of having been silenced via pseudogenization. A single copy of a Panicum sp. rDNA unit present in H. bogdanii had been interrupted by a native transposable element and was surrounded by about 70 kbp of mostly noncoding sequence of panicoid origin. The data suggest that horizontal gene transfer between vascular plants is not a rare event, that it is not necessarily restricted to one or a few genes only, and that it can be selectively neutral.
Keywords: horizontal gene transfer; Genes, Plant; Cell Nucleus; přenos genů horizontální; fylogeneze; Hordeum; Sequence Analysis, DNA; Phylogeny; transposable elements; ribozomální DNA; sekvenční analýza DNA; molekulární evoluce; Evolution, Molecular; buněčné jádro; mezerníky ribozomální DNA; Gene Transfer, Horizontal; DNA rostlinná; DNA, Plant; Panicoideae; lipnicovité; ječmen (rod); Diploidy; DNA, Ribosomal Spacer; DNA, Ribosomal; rostlinné geny; diploidie; Triticeae; Poaceae